2021
DOI: 10.1016/j.heliyon.2020.e05894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanocurcumin and fish oil as natural anti-inflammatory compounds vs. glucocorticoids in a lipopolysaccharide inflammation model on Holstein calves’ health status

Abstract: Curcumin (CUR) and fish oil (FO) are among the most well-known types of natural anti-inflammatory compounds. The aim of this study was to assess the effect of nanocurcumin and fish oil vs. glucocorticoids on Holstein calves' health status. A lipopolysaccharide (LPS) challenge (0.5 μg kg À1 BW) was used to induce an acute phase response.A total of 42 male Holstein calves were randomized into 7 groups: negative control (CON), positive control (LPS, injected once), 250 mg/kg BW per day fish oil þ LPS (FO250), 350… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
(50 reference statements)
2
7
0
Order By: Relevance
“…There was no significant effect of fish oil and curcumin on the level of ID17, while this metabolite was significantly decreased upon dexamethasone treatment (96%) (Figure 5b). This result confirms our earlier findings [24] that there was no effect of fish oil and curcumin on appetite, sickness behavior, and inflammation response following LPS challenge in calves. In contrast, dexamethasone improved sickness behavior and inflammation response in LPS challenged calves [24].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…There was no significant effect of fish oil and curcumin on the level of ID17, while this metabolite was significantly decreased upon dexamethasone treatment (96%) (Figure 5b). This result confirms our earlier findings [24] that there was no effect of fish oil and curcumin on appetite, sickness behavior, and inflammation response following LPS challenge in calves. In contrast, dexamethasone improved sickness behavior and inflammation response in LPS challenged calves [24].…”
Section: Discussionsupporting
confidence: 93%
“…The clinical results of the APR experiment have been reported previously [24]. In brief, repeated measures ANOVA revealed that rectal body temperature (RT), heart rate (HR), respiratory rate (RR), and cytokines were significantly altered (p-value < 0.05) within each group, before and after LPS challenge.…”
Section: Acute Phase Responsesupporting
confidence: 54%
See 3 more Smart Citations